THE INFLUENCE OF CUSTOMER-CENTRIC STRATEGY TOWARD TOURIST SATISFACTION - Agustinawati, Agustinawati; Samsidar, Samsidar; Bahri, Halida; Juliana, Juliana; Pendi, Pendi (CV. Radja Publika, 2021)
This study aims to investigate the infleunce of customer centric marketing mix on satisfaction for tourists in context of Aceh. The Halal tourism destination such as Ujong Blang beach, Seumadu beach, Lancok beach, Pangah Beach, Waduk Jeulikat, Lhok Seulayang, Museum Geudong and Gunung Sala is the latest destination in North Aceh and Lhokseumawe, Indonesia. This destination currently very in great demand by the tourists. A survey questionnaire is used to conduct this study. A sample of 200 tourists participated in the study. The findings reveal the significant positive relationship of three marketing mix elements with tourists’ satisfaction for tourism services in the context of Aceh.